2005
DOI: 10.1081/bip-200062293
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Adaptive Design for Clinical Trials with Survival Data

Abstract: In long-term clinical trials we often need to monitor the patients' enrollment, compliance, and treatment effect during the study. In this paper we take the conditional power approach and consider a two-stage design based on the ideas of Li et al. (2002) for trials with survival endpoints. We make projections and decisions regarding the future course of the trial from the interim data. The decision includes possible early termination of the trial for convincing evidence of futility or efficacy, and projection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…On the other hand, suppose that it is desirable to set a 0 = 0.3, this rule then restricts a 1 = 0.013, more than half of the overall a, and definitely more than 0.005, what we would like to spend for the first stage. Li et al (2002Li et al ( , 2005, when discussing the conditional error functions of Proschan and Hunsberger (1995), have pointed out this fact and proposed a method that enables us to specify a 0 and a 1 independently, thus makes the design even more flexible.…”
mentioning
confidence: 97%
“…On the other hand, suppose that it is desirable to set a 0 = 0.3, this rule then restricts a 1 = 0.013, more than half of the overall a, and definitely more than 0.005, what we would like to spend for the first stage. Li et al (2002Li et al ( , 2005, when discussing the conditional error functions of Proschan and Hunsberger (1995), have pointed out this fact and proposed a method that enables us to specify a 0 and a 1 independently, thus makes the design even more flexible.…”
mentioning
confidence: 97%
“…Chow, Chang, and Pong [15] examined the impact of population shift due to protocol amendments. Li et al, [12] studied a two-stage adaptive design with a survival endpoint, while Hommel et al [16] studied a two-stage adaptive design with correlated data. An adaptive design with a bivariate-endpoint was studied by Todd [17] Tsiatis and Mehta [18] showed that there exists a more powerful group sequential design for any adaptive design with sample size adjustment, For illustration purpose, in what follows, we will introduce the method based on sum of p-values (MSP) by Chang [2,19].…”
Section: Analysis For Category I Adaptive Designsmentioning
confidence: 99%
“…In practice, many interesting methods for Category I designs are available in the literature. These methods include (1) Fisher's criterion for combining independent p-values [6][7][8], (2) weighted test statistics [9] (3) the conditional error function approach [10,11] and (4) conditional power approaches [12].…”
Section: Analysis For Category I Adaptive Designsmentioning
confidence: 99%
“…In adaptive trial design, at the time of the interim analysis: (1) if a "large" treatment effect is observed, the study can be terminated with the rejection of the null hypothesis; (2) if a "small" treatment effect is observed the study is terminated while declaring the treatment futile; or (3) if there is an intermediate treatment effect, the study is continued where the number of patients in the second stage is determined as a function of the observed treatment effect from the first stage (the study sample size is not specified until after the interim analysis). Methods to implement this "two stage" approach have been developed for trials with continuous 17 and time-to-event 19 outcomes.…”
Section: Howard Nonconventional Clinical Trial Designs 805mentioning
confidence: 99%